A qualitative study of institutional review board members’ experience reviewing research proposals using emergency exception from informed consent - McClure, B. (Journal of medical ethics, 2007)
Background: Emergency exception to informed consent regulation was introduced to provide a venue to perform research on subjects in emergency situations before obtaining informed consent. For a study to proceed, institutional review boards (IRBs) need to determine if the regulations have been met. Aim: To determine IRB members’ experience reviewing research protocols using emergency exception to informed consent. Methods: This qualitative research used semistructured telephone interviews of 10 selected IRB members from around the US in the fall of 2003. IRB members were chosen as little is known about their views of exception to consent, and part of their mandate is the protection of human subjects in research. Interview questions focused on the length of review process, ethical and legal considerations, training provided to IRB members on the regulations, and experience using community consultation and notification. Content analysis was performed on the transcripts of interviews. To ensure validity, data analysis was performed by individuals with varying backgrounds: three emergency physicians, an IRB member and a layperson. Results: Respondents noted that: (1) emergency exception to informed consent studies require lengthy review; (2) community consultation and notification regulations are vague and hard to implement; (3) current regulations, if applied correctly, protect human subjects; (4) legal counsel is an important aspect of reviewing exception to informed-consent protocols; and (5) IRB members have had little or no formal training in these regulations, but are able to access materials needed to review such protocols. Conclusions: This preliminary study suggests that IRB members find emergency exception to informed consent studies take longer to review than other protocols, and that community consultation and community notification are the most difficult aspect of the regulations with which to comply but that they adequately protect human subjects.